Plantes médicinales de Mauritanie. Remèdes traditionnels et guérisseurs du Sahara au fleuve Sénégal- a book review - Yebouk, Cheikh (Ethnobotany Research and Applications, 2025)
Plantes médicinales de Mauritanie. Remèdes traditionnels et guérisseurs du Sahara au fleuve Sénégal- Michel Thouzery, Abdellahi Ould Mohamed Vall. Edition : Association Plantes et nomades, Paris2011. 287pp. Price: € 32 .-, ISBN 9 782746-633643, French Plantes médicinales de Mauritanie. Remèdes traditionnels et guérisseurs du Sahara au fleuve Sénégal “Medicinal Plants of Mauritania: Traditional Remedies and Healers from the Sahara to the Senegal River” delves into the medicinal plant practices of local communities and traditional healers, meticulously documenting their methods. It also explores how these plants might enhance contemporary health care systems, based on fifteen years of field research. By looking at the ecological, pharmacological, and ethnobotanical aspects of these practices, this method effectively combines old knowledge with modern scientific knowledge. Furthermore, it highlights the challenges of maintaining plant resources amid increasing desertification.